Izboljšanje mehanskih lastnosti spajkanih spojev s kompozitno spajko - Zorc, Borut (Kovine zlitine tehnologije, 1995)
Mechanical properties of brazed joints can be improved in several ways. The so-called composite joint permits a simultaneous solution of some of the problems related to brazed joints. An approach to carrying out composite joints and alayses some ideas on the structure of the joints of which it is believed that they can be carried out in this way is described. Reactions among all the constituent parts of the brazed joint are important, therefore the term composite joint has a broader meaning as in composite materials.
Keywords: varjenje; spajkanje; spoji; mehanske lastnosti